Cloning of chicken IL2 cytokine gene into pNZ:vig vector - Zaini, Noor Ain (2015)
pNZ:vig vector is a bicistronic vector isolated from Lactococcus lactis that carrying VP2 gene and GFP expressed under IRES-mediated translation. IL-2 cytokines is a molecule produce by T-helper cells in response to antigen attack. Despite such drawbacks of conventional live vaccines, it has potential of utilize food grade Lactococcus lactis as a live vector for the delivery of vaccine. To obtain a natural vaccine-enhancing molecule, in order to stimulate the proliferation of T-cells in chicken infected with IBDV, partial IRES-IL2 gene was successfully designed to introduce into pNZ:vig vector. This combination covers the requirement to improve the potency of the immune response against IBDV. In this study, GFP cassette was removed from the vector to clone IL-2 cytokine gene. A commercial vector pIDT (Clontech) that carry partial IRES-IL2 was maintained and propagated by using Escherichia coli TOP10. Positive transformants were confirmed by using colony PCR and concurrently validated further by agarose gel electrophoresis analysis. Forward and reverse primers were designed to amplify partial IRES-IL2 fragment by using PCR. Gel electrophoresis confirmed the estimated size of the partial IRES-IL2 fragment was approximately 700 basepairs. Meanwhile, pNZ:vig vector was extracted from L.lactis NZ9000 by plasmid extraction and subjected to restriction enzyme digestion by using restriction enzymes Kpn1 and Nar1. Digested pNZ:vig vector was verified by agarose gel electrophoresis and the results depicted the expected size of the vector was approximately 6000 basepairs. Restriction enzyme digestion for pIDT plasmid needs further optimization to obtain partial IRES-IL2 fragment. The ligation of partial IRES-IL2 fragment into pNZ:vig vector was not successful thus needs further optimization.